EFFECT OF DE-OILED RICE BRAN ON THE CARCASS CHARACTERISTIC AND BLOOD PROFILES IN BROILERS* (Indian Journal of Animal Production and Management, 2014)
One hundred nos. of twenty day old commercial broiler chicks were divided into four groups (T0 - control, T1, T2, T3) of 30 chicks. Each were allotted to four iso-nitrogenous dietary treatments, viz. D0, D1, D2 and D3, containing 0 (control), 10, 15 and 20 per cent of DORB for 6 weeks. At the end of the feeding period, 5 birds from each group were slaughtered for study of the carcass characteristics. The dressing percentage, eviscerated yield and giblet yield were comparable among the groups. The percent moisture, protein, fat and total ash content of the meat did not vary significantly (P>0.05) among the groups. The blood glucose, total serum protein, albumin and albumin:globulin (A:G) ratio were comparable among the groups.
Keywords: DORB; Broilers; Carcass characteristics; Blood profiles